Elementary School Students' Critical Thinking Abilities in Relation to Their Language and Reasoning Abilities - Alfi Sayida, Reza Rosita; Sutomo, Moh; Saihan, Saihan (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2024)
Abstract Critical thinking skills in science learning are important competencies for elementary school students in facing the challenges of the 21st century. This study aims to describe the critical thinking skills of grade V students in science learning at MI Miftahul Huda Banyuwangi. The method used was descriptive qualitative with a phenomenological approach. The results showed that 18 out of 26 students obtained a percentage of <50%, which included a relatively weak category. The conclusions of this study are: (1) The critical thinking skills of fifth grade students in learning science are influenced by internal and external factors. Internal factors include student characteristics, reading ability, learning motivation, writing ability, and student habits. External factors include the organization of learning by teachers and habituation carried out by teachers to students. (2) The critical thinking skills of fifth grade students in science learning are relatively weak. (3) Low critical thinking skills are caused by students' low language and reasoning skills.Keywords: Critical Thinking, Elementary School, Language and Reasoning Abilities